Inventory and Diversity of Butterflies (Lepidoptera: Papilionoidea) in Puthuk Panggang Welut Tourism Area, Mojokerto, East Java - Anida Reza Fahlefi; Misbakhul Munir; Saiful Bahri; Siska Umami; Nasywa Sayyida Amaliyah; Anggi Syavira Oktaviana; Muhamad Azmi Dwi Susanto (Universitas PGRI Silampari, 2024)
Tourism area is a tourism site that utilises the potential of natural resources, tourism areas support butterfly habitats, one of which is in Puthuk Panggang Welut Tourism, Mojokerto. The Puthuk Panggang Welut area has a natural ecosystem and there has been no previous research related to butterfly diversity. The purpose of this study was to determine the diversity of butterfly species (Lepidoptera: Papilionoidea) in the Puthuk Panggang Welut tourist area, Mojokerto. The capture of specimens was carried out by the transect method using an insect net (sweep net). Based on observations obtained, five families, namely Hesperiidae, Lycaenidae, Nymphalidae, Papilionidae, and Pieridae, the number of species obtained, as many as 30 species from five families and 221 individuals, with a value of H' = 3.07 so that it can describe the quality of the environment at Puthuk Panggang Welut Tourism, is classified as a high level of diversity. In addition, on the tourist track, the species Troides helena was found, which is one of a protected species.